The Influence of Leadership and Organizational Culture on The Performance of Educators of Women Police Schools (Sepolwan) Polri Lemdiklat - Dangsi Mepri; Ma’ruf Akbar; Matin Matin (Peneliti.net, 2021)
This research was conducted with the aim of knowing whether there is an influence of leadership behavior and organizational culture on the performance of educators at the Women's Police School (Sepolwan) Lemdiklat Polri. Measuring the performance of educators at Sepolwan Lemdiklat Polri is based on factors of leadership behavior and organizational culture. The method used in this research is survey research with a quantitative approach. The analysis used is path analysis, which tests and measures the direct effect of one variable on another. The population in this research was 158 respondents. The sample in this study was taken using a simple random technique and a sample technique from Slovin with the calculation results of 78 educators. The finding of the research is that leadership has a positive direct effect on the performance of the National Police's teaching staff. Good leadership will have a positive influence on improving the performance of the National Police's teaching staff. Organizational culture has a positive direct effect on the performance of Polri's educators. The stronger the organizational culture of the National Police, the better the performance of its educators. Organizational culture has a positive direct effect on the performance of the National Police's teaching staff. The leadership of a qualified National Police principal can have an impact on enhancing a conducive organizational culture.